The advancement of imaging in diagnosis of prostate cancer - Osuchowski, Michał; Aebisher, David; Gustalik, Joanna; Bartusik-Aebisher, Dorota; Kaznowska, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. Multiple imaging methods have been used to stage prostate carcinoma. Some of them are easily accessible, others very accurate. The advancements over many years have been taken under consideration and now every imaging method has a specific role in the diagnosis of this malignancy. Aim. There are over 1,100,000 cases of prostate carcinoma diagnosed every year around the world. Imaging examinations have to be introduced to accurately stage, and therefore properly treat this disease. This review concentrates on advantages and disadvantages of different imaging methods. Material and methods. The literature search was performed. Results. Imaging methods serve specific goals. TRUS is recommended for acquiring biopsy specimen due to high accessibility and low cost of the examination. Conclusion. The best tool for staging prostate carcinoma and finding suspicious lesions when attempting second biopsy is mpMRI or bpMRI.
Dorota Bartusik-Aebisher acknowledges support from the National Center of Science NCN (New drug delivery systems-MRI study, Grant OPUS-13 number 2017/25/B/ST4/02481).
Keywords: MRI; PET; prostate carcinoma